What Do We Know About Black and Minority Ethnic (BAME) Participation in UK Higher Education?. Issue 1 (4th January 2022) - Arday, Jason; Branchu, Charlotte; Boliver, Vikki
Abstract : Here, we offer a synthesis of recent evidence and new developments in relation to three broad aspects of Black and minority ethnic (BAME) students' participation in UK higher education (HE). First, we examine recent trends in ethnic group differences in rates of access to, success within, and positive destinations beyond HE. Secondly, we examine the nature of UK universities as exclusionary spaces which marginalise BAME students in a myriad of ways, not least through curricula that centre Whiteness. Finally, we consider the impact of the marginalisation of BAME students on mental health. We argue that progress towards race equality in each domain has been hampered by white-centric discourses which continue to identify BAME students and staff as 'other'. We highlight the important roles that academic communities and HE policy-makers have to play in advancing ethnic equality in UK universities.